Analysis of The Occurrence of Damage To Crane Operations on Board Km. Lotus Ungu - Sarifuddin Sarifuddin (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
The smooth maintenance and repair of diesel main engines requires complete and adequate equipment. Hoist cranes are equipment used to lift and move engine components that cannot be moved by human labor. With a hoist crane on board, the machinist on board is easier to lift diesel main engine components such as cylinder heads, pistons, and cylinder liners when carrying out maintenance and repairs. To support the process of lifting diesel main engine components during maintenance and repair, the hoist crane must be in good condition. The main point of a good hoist crane is that the hoist crane can lift loads up to 4 tons. The method that the author uses to make this scientific work is to use a qualitative descriptive method. In this scientific work, the instruments used to produce descriptive data are observation, interviews and documentation. Carrying out these steps is expected to find the problems that cause damage to the hoist crane. Hoist crane damage caused by high temperature electromotor can be prevented by performing maintenance according to the planned maintenance system.